DESIGN A WEBSITE USING FRONTPAGE 2000 FOR THE SALE OF AUDIO CASSETTES IN THE DELTA BLUES MUSIC KELAPA GADING - Wisnu Wardhana; Ir. Fitri Sjafrina, MM (Jurnal Sistem Informasi, 2001)
E-commerce or electronic commerce is one of the promotional media and internet - based transactions that are now starting to rage. delta blues music as one record store, trying to promote its products to the Internet by creating a website, in which there is information about the tapes, CDs, VCDs or DVDs that have been grouped by type, price lists and how to order. Use of print media to promote the more expensive price, so the delta blues music performed mengehentikan promotion in newspapers or magazines. ordering via the Internet also requires a check of credit card numbers that must wait for confirmation from the relevant bank for 24 hours. See things in those stores writer tries to help design the website with Microsft FrontPage 2000, in addition to the tools contained in it can be designed according to the desires of the shop, the way reservations contained therein also allows buyers to emlakukan transaction without having to come to the store.